Is Prophethood Superfluous?Conflicting Outlook on the Necessity of Prophethood between Badiuzzaman Said Nursi and Some Muslim Philosophers - Fauzan Saleh (Al-Jami'ah: Journal of Islamic Studies, 2015)
As early as tenth century, Abū Bakr al-Rāzī (d. 925), a notable figure in Islamic philosophy, claimed that prophethood is entirely superfluous, since God imparted the gift of reason to humankind, and reason is enough to guide them. Al-Rāzī’s skeptical view sounds provocative, and thus worthy of further study. However, some other philosophers, like al-Farābī, Ibn Sīnā and Ibn Maskawaih, acknowledge the necessity of prophethood for the guidance of human life. Their idea, though formulated in different reasoning from the one held by Muslim theologians, indicates their acceptance of the authority of divine revelation. On the other hand, Said Nursi, one of the greatest Muslim reformers in the modern time, maintains that since “divine power does not leave the ant without leader, or bees without a queen, it surely would not leave mankind without prophet or code of law.” After all, the order of the world necessitates the existence of the prophets to preserve its solidity. This article will scrutinize more critically Nursi’s idea on the necessity of divine revelation that would enlighten human path to truth, to be compared with some ideas held by Muslim philosophers in discussing the relationship between reason and revelation, and its corollaries.[Filsuf besar dari abad ke-10, Abū Bakr al-Rāzī (w. 925), menyatakan bahwa diutusnya seorang nabi sebenarnya tidak perlu lagi, karena Tuhan telah menganugerahkan akal pada manusia yang akan mampu membimbing mereka. Pandangan skeptis dari al-Rāzī ini terdengar provokatif dan perlu dieksplorasi lebih lanjut. Namun, beberapa filsuf seperti al-Farabi, Ibnu Sina, dan Ibn Maskawaih mengakui perlunya nabi untuk membimbing manusia. Pandangan para filsuf ini, meski dengan nalar yang berbeda dengan para ahli teologi, mengindikasikan penerimaan terhadap otoritas wahyu ketuhanan. Di sisi lain, Said Nursi, seorang pemikir-reformis modern, menyatakan bahwa karena “kuasa Tuhan tidak pernah membiarkan sekawanan semut tanpa pemimpin, atau sekelompok lebah tanpa ratunya, maka pastilah manusia juga tidak akan dibiarkan tanpa seorang nabi atau syariat.” Lebih dari itu, tata dunia juga memerlukan kehadiran seorang nabi untuk menjaga soliditasnya. Tulisan ini akan melihat secara lebih dalam dan kritis mengenai pemikiran Said Nursi tentang pentingnya wahyu ketuhanan untuk menerangi langkah manusia menemukan kebenaran; kemudian dibandingkan dengan pandangan filsuf-filsuf muslim lainnya dalam membincang keterkaitan nalar dan wahyu dengan segala konsekuensinya.]